SOSIALIASI PELAKSANAAN PENGENALAN LAPANGAN PERSEKOLAHAN I TAHUN AJARAN 2020/2021 - Baziduhu Baziduhu Laia; Restu Restu Damai Laia; Eka Eka Periaman Zai; Impiani Impiani Zagoto; Ujianhati Ujianhati Zega; Darmawan Darmawan Harefa; Kalvintinus Kalvintinus Ndruru (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of this service is to socialize the introduction of the school field. This is an activity contained in the guidebook used by all students in semester IV. This socialization aims to provide an overview of the steps in carrying out the Field introduction activity for Persekolaha I which is the first stage in the introduction of the School of Education Field for the Undergraduate Education Program at STKIP Nias Selatan, especially in the process of preparing professional teachers for the undergraduate education program, in the form of assigning students to implement learning outcomes through observing the learning process at school. The scope of implementation of the Introduction to Persekolaha Field, observation activities, analysis and direct appreciation of activities related to school culture, school management, and school dynamics as an educational and learning institution.